Photorelease of incarcerated caged acids from hydrophobic coumaryl esters into aqueous solution - Kamatham, Nareshbabu (2017)
Photolysis of aqueous solutions of carboxylic acid esters of 7-(methoxycoumaryl)-4-methanol included within the capsule made up of two molecules of octaacid released the acids in water. The trigger 7-(methoxycoumaryl)-4-methyl chromophore remains within octaacid either as the alcohol or as an adduct with the host octaacid through a hydrogen abstraction process. The method established here offers a procedure to release hydrophobic acid molecules in water at will in a timely manner with light. In addition, the system offers an unanticipated opportunity to probe the mechanistic dichotomy of a diradicaloid intermediate expressing both radical and ionic behavior when generated by coumarylmethyl ester photolysis in a hydrophobic environment.